(untitled) (Global Journal of Management and Business Research, 2018)
Literature on camel milk market channel choices has been thin, especially in pro-poor pastoral/agro-pastoral area of sub-Saharan Africa, as a result its prudent to note that none of past studies identified factors affecting camel milk market channel choices in Eastern Ethiopia even though camel milk market access is pivotal to transform livelihood of people who live in arid and semi-arid areas of Ethiopia. Therefore, the study seeks to determine factors influencing camel milk marketing channel choice in Gursume and Babile districts of Eastern Ethiopia, with the aim of enhancing camel milk competitiveness. Data were collected from 92 camel milk producers’ pastoral/agro-pastoralist by using two-stage stratified sampling. Multinomial Logit model was employed for analyzing data. Multinomial Logit model result indicated that, compared to assembler market channel outlet (base channel), the likelihood of accessing consumer market outlet was higher among pastoral/agro-pastoral who have higher educational level, better livestock extension services, better milk market information and higher income from none dairy source. The likelihood of accessing commission man milk marketing channel choice was higher for households who wanted better milk price offered by commission agent as compared to the base channel. Compared to accessing assembler market outlet, the likelihood of accessing retailer milk market outlet was higher for those who have better dairy extension services and for those who were far away from milk market.